2016
DOI: 10.1371/journal.pone.0151502
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of 1,3-Dihydroxy-2-Methylanthraquinone and the Ethyl Acetate Fraction of Hedyotis Diffusa Willd against HepG2 Carcinoma Cells Mediated via Apoptosis

Abstract: Hedyotis Diffusa Willd, used in Traditional Chinese Medicine, is a treatment for various diseases including cancer, owing to its mild effectiveness and low toxicity. The aim of this study was to identify the main anticancer components in Hedyotis Diffusa Willd, and explore mechanisms underlying their activity. Hedyotis Diffusa Willd was extracted and fractionated using ethyl acetate to obtain the H-Ethyl acetate fraction, which showed higher anticancer activity than the other fractions obtained against HepG2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Treatment with total flavones extract from H. diffusa could reverse the invasion of MHCC97-H cells in epithelial-mesenchymal transition induced by TGF-β1 at the dose of 200µg/mL, and the effect might be carried out by decreasing the level of E-cadherin protein and increasing the expression of vimentin protein [71]. Li et al found that both 1,3-Dihydroxy-2-Methylanthraquinone (79 and 157 µmol/L) and ethyl acetate extract (100 and 200 µg/mL) induced apoptosis on HepG2 cells, resulting in upregulation of Bax, p53, Fas, FasL, p21 and cytoplasmic cytochrome C levels and caspase-3, -8, -9 proteases activities, while downregulation of Bcl-2, mitochondrial cytochrome C, cyclin E and CDK 2 in a dose-dependent manner [72]. Nine compounds from H. diffusa, namely, ethyl 13 (S)-hydroxy-chlorophyllide a, 2-methyl-3-methoxy anthraquinone, 2-hydroxymethyl anthraquinone, 2-hydroxy-3-methyl anthraquinone, 2-hydroxymethy-1-hydroxy anthraquinone, 2-hydroxy-1-methoxy anthraquinone, 2-hydroxy-3-methyl-1-methoxy anthraquinone, oleanolic acid and ursolic acid, have been researched for their anti-liver cancer effect within the concentration range from 1 to 200 µM.…”
Section: Anti-liver Cancer Activitymentioning
confidence: 99%
“…Treatment with total flavones extract from H. diffusa could reverse the invasion of MHCC97-H cells in epithelial-mesenchymal transition induced by TGF-β1 at the dose of 200µg/mL, and the effect might be carried out by decreasing the level of E-cadherin protein and increasing the expression of vimentin protein [71]. Li et al found that both 1,3-Dihydroxy-2-Methylanthraquinone (79 and 157 µmol/L) and ethyl acetate extract (100 and 200 µg/mL) induced apoptosis on HepG2 cells, resulting in upregulation of Bax, p53, Fas, FasL, p21 and cytoplasmic cytochrome C levels and caspase-3, -8, -9 proteases activities, while downregulation of Bcl-2, mitochondrial cytochrome C, cyclin E and CDK 2 in a dose-dependent manner [72]. Nine compounds from H. diffusa, namely, ethyl 13 (S)-hydroxy-chlorophyllide a, 2-methyl-3-methoxy anthraquinone, 2-hydroxymethyl anthraquinone, 2-hydroxy-3-methyl anthraquinone, 2-hydroxymethy-1-hydroxy anthraquinone, 2-hydroxy-1-methoxy anthraquinone, 2-hydroxy-3-methyl-1-methoxy anthraquinone, oleanolic acid and ursolic acid, have been researched for their anti-liver cancer effect within the concentration range from 1 to 200 µM.…”
Section: Anti-liver Cancer Activitymentioning
confidence: 99%
“…Therefore, the use of TCM promising when treating cancer cell drug-resistance and may allow for improved treatment of cancer. Hedyotis diffusa Willd (HDW) is a major component of TCM with potent anti-cancer effects on various cancers, such as ovarian, hepatocellular and cervical cancer (18)(19)(20)(21). Previous studies have also demonstrated that HDW may inhibit CRC cell proliferation (22)(23)(24)(25)(26).…”
Section: Hedyotis Diffusa Willd Inhibits Proliferation and Induces Apmentioning
confidence: 99%
“…Treatment involves surgery, and chemotherapy is the main procedure following, but it has adverse side effects with low cure rate and high secondary failures. So the scientists researched effective anticancer drugs with less toxic effects (Li et al, 2016). Phytochemicals from plants used as an alternative drug for cancer treatment along with chemotherapy (Vanitha and ., 2017) Plants sources play a great role, and many plant-derived compounds like polyphenols, lavonoids, and terpenoids are of much nutritional and health bene its and immensely studied for their potent useful effects on humans (Pan MH et al, 2008).…”
Section: Introductionmentioning
confidence: 99%